The role of monitoring the level of matrix metalloproteinase 3 in patients with rheumatoid arthritis on anti-B-cell therapy - A. S. Avdeeva; V. V. Rybakova; O. G. Alekseeva; E. L. Nasonov (Научно-практическая ревматология)
Objective: to evaluate the role of monitoring the level of matrix metalloproteinase 3 (MMP-3) in patients with rheumatoid arthritis (RA) during anti-B-cell therapy.Material and methods. The study included 54 patients with a reliable diagnosis of RA. Depending on the therapy, all patients were divided into two groups: 34 patients received the original RTM (group 1) and 20 patients – biosimilar (group 2) in a total dose of 1200 mg according to the standard scheme. The concentration of MMP-3 in serum was measured by enzyme immunoassay using a kit of reagents from Invitrogen (USA).Results. The level of MMP-3 in patients with RA was significantly higher than in healthy donors, its median was 42.9 [10.0; 110.7] and 7.8 [5.5; 11.8] ng/ml, respectively (p<0.05). 12 and 24 weeks after the first infusion of the original RTM, there was a statistically significant decrease in the concentration of MMP-3, amounting to 80% of the initial level. Against the background of the use of the RTM biosimilar, after 12 and 24 weeks, a statistically significant decrease in the concentration of MMP-3 was observed, which was 46.8 and 59% of the basal level, respectively. According to the ROC analysis, it was found that the basal level of IL-6 more than 100.0 pg/ ml and the level of MMP-3 more than 78.6 ng/ml were associated with the preservation of inflammatory activity by the 24th week of therapy with the RTM biosimilar with a sensitivity of 85% and 57% and a specificity of 62% and 61.5%, respectively. Conclusion. Determining the level of MMP-3 in patients receiving anti-B-cell therapy is important for a more objective assessment of disease activity and predicting the effectiveness of treatment. Key words: rheumatoid arthritis, matrix metalloproteinase 3, anti-B-cell therapy, rituximab biosimilar>˂ 0.05). 12 and 24 weeks after the first infusion of the original RTM, there was a statistically significant decrease in the concentration of MMP-3, amounting to 80% of the initial level. Against the background of the use of the RTM biosimilar, after 12 and 24 weeks, a statistically significant decrease in the concentration of MMP-3 was observed, which was 46.8 and 59% of the basal level, respectively. According to the ROC analysis, it was found that the basal level of IL-6 more than 100.0 pg/ ml and the level of MMP-3 more than 78.6 ng/ml were associated with the preservation of inflammatory activity by the 24th week of therapy with the RTM biosimilar with a sensitivity of 85% and 57% and a specificity of 62% and 61.5%, respectively.Conclusion. Determining the level of MMP-3 in patients receiving anti-B-cell therapy is important for a more objective assessment of disease activity and predicting the effectiveness of treatment.